Fuzzy Logic Controller for Stabilizing the Rolling Movement of Uav Bicopter - Fahmizal, Fahmizal; Nugroho, Hanung Adi; Cahyadi, Adha Imam; Ardiyanto, Igi (ICIC International, 2023)
This paper describes the design of a fuzzy logic controller (FLC) for stabilizing the rolling motion of an unmanned aerial vehicle (UAV) Bicopter. Rolling motion control is part of the inner loop (attitude) control in UAV Bicopter, which is very important to control for achieving rapid settling time and stability. The Bicopter is a nonlinear, unstable, underactuated system and hard to model clearly in mathematics. In order to stabilize the rolling motion of a UAV Bicopter, this research proposes an embedded FLC. The developed FLC uses the Mamdani approach and varied rule base. The UAV Bicopter was placed on a test bed with a Teensy 3.6 microcontroller to validate our approach. The results of the experiments and tests were presented to demonstrate the proposed controller's validity.